Analysis and Investigation of the Cause of Increased Energy Consumption in a Centrifugal Dewatering Plant - Kurbonov, O. M.; Safarova, M. D. (Researchparks Publishing, 2023)
Today, it is estimated that up to 20-25% of the world's electricity consumption is for pumping equipment. Up to 85% of the operating costs of pumps are electricity costs. The E.F. of pumping systems often does not exceed 10-20%, while the E.F. of pumps is 50-90% [1,2]. Since reducing energy consumption is a priority for the company, economic efficiency in general is directly linked to the use of pumping equipment. In this paper we discuss the current problems in analysing and investigating the pressure characteristics of centrifugal pumps.